A comprehensive study of char reaction kinetics: Does CO always promote NO reduction on char surface?. (15th February 2022) - Ke, Xiwei; Jiang, Ling; Li, Yiran; Yang, Hairui; Lyu, JunFu; Zhang, Man
Highlights: CO has the dual nature of promotion and inhibition effects on char-NO reactivity. Char plays a catalytic role in the NO reduction process at high CO concentration. The increase of coal rank leads to the decline in char-NO reactivity. Langmuir adsorption theory is adopted to analyze the experimental phenomena. A simple expression for calculating NO reduction rate on chars was provided. Abstract: This investigation focuses on the NO reduction process over chars and quantifies the effects of CO on char-NO reactivity under different conditions. Kinetic data were measured in a lab-scale fixed-bed reactor at temperatures between 1023 K and 1223 K, involving three coal chars with coal ranks ranging from lignite to anthracite. Experimental results show that CO can promote the reduction of NO over chars at low temperatures. However, there is a significant decrease in NO conversion rate at high temperatures compared to the case without CO present in the gas. The promotion or inhibition effects of CO on char-NO reactivity will become more obvious if the CO concentration is higher. Moreover, the consumption rate of NO is about the same as the generating rate of CO2 under high-level CO conditions, while a considerable amount of CO is generated during the direct reduction of NO by carbon. Further analysis based on Langmuir adsorption theory also indicates that char plays a catalytic role in NO reduction rather than acting as a reactant when CO is added. In addition, under the same temperature and gas conditions, the reactivity of SC lignite char is roughly five times higher than that of HP bituminous char and ten times higher than that of WH anthracite char, namely, the increase of coal rank leads to the decline in char-NO reactivity. Besides, the char made from higher rank coal has a broader range of temperature at which the CO presents a positive effect on NO reduction. Finally, a simple expression was proposed to calculate the NO reduction rate on char surface based on the experimental data, which can be easily applied in the description of nitrogen chemistry for fluidized bed combustion.